A PRACTICE OF OPEN DATA ADOPTION TO «PROGRAMMING» COURSE OF «SOFTWARE ENGINEERING» BACHELOR PROGRAM - Olga V. Maksimenkova; Vadim V. Podbelskiy (Образование и наука)
Abstract. The aim of the publication is to show the possibilities of use of open data in teaching courses of programming.Methods. The results of adoption of the technique presented in the publication to the process of training in programming at the first year of the course «Program Engineering» are received by a comparative research and analysed by methods of descriptive statistics.Results and scientific novelty. The technique of the use of open data sets when developing training and control tasks on programming for students of a bachelor degree of information and technological educational program specialization is offered; standard tasks templates are presented.The application of open data in the educational purposes is a rather new direction in education that considerably enables to improve the quality of training of an expert in the field of computer sciences: to bring closer educational tasks to real; to increase variability of control tasks; to increase motivation of students. However, along with positive characteristics of the presented method, there are some difficulties of the method introduction in educational process. The authors have formulated the problems arising when using open data; possible ways of their decision are shown.Practical significance. The results received during the research show the possibilities of further expansion of application of open data in education. The described practical experience of training in programming can be partially or completely used by teachers of other training courses.